Pharmacological Characteristics of Porcine Orexin 2 Receptor and Mutants - Liu, Min; Min, Tianqi; Zhang, Haijie; Liu, Yuan; Wang, Zhiqiang (Frontiers in Endocrinology, 2020)
Orexin receptors (OXRs) play a critical regulation effect in central control of food intake, maintenance of sleeping states, energy metabolism and neuroendocrine. However, most previous studies focus on the sleep-promoting functions of OXRs in human beings, the potential value in enhancing food intake for livestock breeding is not fully exploited. In this study, we successfully cloned porcine orexin 2 receptor (pOX2R) complementary DNA and constructed four pOX2R mutants (P10S, P11T, V308I and T401I) by site-directed mutagenesis, and their functional expression were further confirmed through western blot analysis. Pharmacological characteristics of pOX2R and their mutants were further investigated. These results showed that P10S, P11T and T401I mutants had decreased cAMP signaling with orexin A, whereas only P11T mutant decreased under the stimulation of orexin B. Besides, only P10S displayed a decreased calcium release in response to both orexin ligands. Importantly, these mutants exhibited decreased phosphorylation levels of ERK1/2, p38 and CREB to some degree compared with wild type pOX2R. Collectively, these findings highlight the critical role of these mutations in pOX2R signaling, and expand our understanding of molecular and pharmacological characterization of pOX2R.